ANALISIS DETERMINAN YANG MEMPENGARUHI BIDAN DESA DALAM KETEPATAN RUJUKAN PADA KASUS PREEKLAMPSIA/EKLAMPSIA DI KABUPATEN BANYUMAS - Suryandari, Artathi Eka; Trisnawati, Yuli (Bidan Prada: Jurnal Publikasi Kebidanan Akbid YLPP Purwokerto, 2014)
Preeclampsia is one of the cases of pregnancy disorders that can cause morbidity and mortality for both mother and baby, occurred over 20 weeks of age and can progress to eclampsia . Early diagnosis and treatment is very important to be done in reducing mortality . Maternal Mortality in Banyumas regency period January to November 2013 was 33 cases in which 9 cases because of preeclampsia. This study aims to find out the determinants that affect the accuracy of the midwife in reference to the case of pre-eclampsia / eclampsia in Banyumas district, using a quantitative approach with a cross-sectional design. Samples were taken by cluster random sampling by 77 midwives. Data analysis was performed using univariate and bivariate chi square. The majority of the village midwife aged > 30 years 50.6 %, most of the midwife has a long working > 5 years as many as 62.3 %, knowledge midwife in Banyumas of pre -eclampsia/eclampsia is good for 62.33 %, the attitude of the respondents showed 80.5 % to be good in the handling of pre -eclampsia/eclampsia. There is no relationship between age (0.721), duration of employment (0.703), knowledge (0.072) and attitude (0.168) with a precision reference midwife in cases of pre -eclampsia/eclampsia in Banyumas district . Keywords : determinants (age , duration of work , knowledge and attitudes) , the accuracy of references in the case preeklampsi/eclampsia